2020
DOI: 10.29262/ram.v67i1.700
|View full text |Cite
|
Sign up to set email alerts
|

Costo anual de la atención médica de pacientes con dermatitis atópica moderada a grave en México. Estudio multicéntrico

Abstract: Antecedentes: En México se desconoce el impacto económico de la atención médica de los pacientes con dermatitis atópica.Objetivo: Determinar los costos médicos directos anuales del tratamiento de pacientes con dermatitis atópica moderada y grave que se atienden en el Instituto de Seguridad y Servicios Sociales de los Trabajadores del Estado, y las principales variables asociadas.Métodos: Estudio multicéntrico de cohorte retrospectiva. Se revisaron los expedientes clínicos de pacientes con dermatitis atópica cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Literature on current cost analyses in adult AD stratifying for different patient groups is rare. In a study from Mexico, higher costs were associated with younger patients with comorbidities and with a diagnosis of depression 9 . Further studies aim predominantly at severity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Literature on current cost analyses in adult AD stratifying for different patient groups is rare. In a study from Mexico, higher costs were associated with younger patients with comorbidities and with a diagnosis of depression 9 . Further studies aim predominantly at severity.…”
Section: Introductionmentioning
confidence: 98%
“…In a study from Mexico, higher costs were associated with younger patients with comorbidities and with a diagnosis of depression. 9 Further studies aim predominantly at severity. A study from Japan found increasing costs for higher severity grades.…”
Section: Introductionmentioning
confidence: 99%